Chapter Les tableaux maudits, en France et en Russie - Gonneau, Pierre (Biblioteca di Studi Slavistici, 2017)
I. Repin's "Ivan the Terrible and his son", exhibited in 1885, in a very tense social and political context, sparked off fierce reactions. While the Itinerant painter Kramskoj is enthusiastic, the ge-neral-prosecutor of the Holy Synod, K. Pobedonoscev, finds the painting "simply repulsive". In France a similar scandal was caused by Gericault's "Raft of the Medusa" (1819). It represents the last instants of the martyrdom of the survivors of the Medusa's shipwreck (1816). Repin's painting, unlike that of Gericault, keeps on arousing a great hostility nowadays in conservative Russian circles.